Influence of isobutanol fuel additive in B40 palm oil methyl ester on engine performance of a diesel engine - N. H., Badrulhisam; Malek, O. A.; Muhammad Yusri, Ismail; Abdul Adam, Abdullah (Faculty Mechanical Engineering, UMP, 2025)
Modern concerns of pollution and the depletion of fossil fuels have drawn much research to alternative energy sources, and biodiesel is a prime example. Biodiesel special properties, such as cetane number higher than that of other diesel fuels, and volatility lower than that of other diesel fuels, can influence diesel combustion and inject fuel systems with the potential for power reduction and nitrogen oxides emissions. This study focuses on palm oil methyl ester (POME) biodiesel and used isobutanol as additives to investigate the potential for the improvement of engine performance. This experiment is precisely conducted from 2000 to 3000 RPM with the data step of 200 RPM. The fuel blends of 5%, 10%, 15%, and 20% isobutanol with B40 (POME) on a diesel engine. The reference fuel will be standard diesel. Among the tested fuels, the B40ISO10 blend achieved the highest torque at 2200 RPM and delivered peak brake power at 3000 RPM, highlighting its efficiency at mid to high engine speeds. While diesel performed well at lower RPMs due to its high calorific value, biodiesel blends, particularly those with isobutanol exhibited improved performance characteristics. Notably, B40ISO15 consistently showed lower brake specific fuel consumption, indicating better fuel economy at higher RPM. Additionally, B40ISO20 displayed significant efficiency gains at increased speeds. These findings suggest that carefully formulated isobutanol enriched biodiesel blends can provide an effective balance of engine performance and fuel efficiency.